Permasalahan Pemberdayaan Masyarakat Pertanian Melalui Usaha Tani di Nagari Pasir Talang - waza karia akbar (Jurnal Community, 2020)
The agricultural sector is the main center in rural areas. this happens because the community works to cultivate the land in their environment. With the formation of farmer groups, community agricultural activities will be more structured. this can be found in the community in Nagari Pasir Talang. the community at work is more structured. but all things did not go well because there were obstacles that must be overcome so that it is interesting to research. This study uses a qualitative type in data collection. theory developed by Robert K Merton. The results showed that the community's capacity was still weak in developing and managing a farm which was formed in the form of farmer groups. so that there are farmer groups that can survive and some die by themselves. The management ability of the community is still very weak in the citrus farmer groups in Nagari Pasir Talang.